THE EFFECTIVENESS OF EDMODO TO IMPROVE STUDENTS’ WRITING SKILL OF RECOUNT TEXT AT THE ELEVENTH GRADE OF SMK NEGERI 1 BLEGA - Moh. Safik; Maulana Yusuf Aditya (Penerbit STKIP PGRI Bangkalan, 2022)
The advancement of technology provides education with various solutions to create new learning environments. Edmodo is a learning platform believed to offer a solution in the teaching of English, particularly for teaching writing. This research was aimed to investigate how Edmodo as a learning platform, in a blended learning setting, was implemented in teaching writing in its combination with Genre-based Approach, how Edmodo facilitated students’ engagement, and how students perceived the use of Edmodo in teaching and learning activities. This research employed a quantitative approach with pre-experimental design. The research involved 27 participants. This study aimed at finding the significant difference in students’ writing skill in recount text before and after using Edmodo App. The students showed various responses towards the use of Edmodo based on the uses framework. the score of the upper stage -1.828. The score of t-value is -3.105 and the degree of freedom is 26. The P-value was 0.005< α was 0.05. It means that Ha was accepted and Ho was rejected. Some issues on the use of Edmodo identified in this research were bandwidth, confusion in using Edmodo, incompatibility of smartphone applications, and students’ lack responsibilities for learning.